Thermodynamic performance assessment and application feasibility analysis of small heat pump water heater using CO2/R41 azeotropy mixture as refrigerant for sustainable development - Wang, Dong; Li, Mengxue; Gu, Zhipan; Mei, Shengong; Deng, Sensen; Lu, Yuehong; Yu, Fangwen (Frontiers in Energy Research, 2023)
In order to improve the application possibility of CO2/R41 azeotropy mixture in refrigeration industry, the optimum mass ratio of composition is defined and determined according to the thermodynamic property and safety. On the basis of the first and second laws of thermodynamics, a model is proposed to evaluate and comprehensively compare the performance among a single-stage transcritical cycle with a throttling valve using CO2/R41 azeotropy refrigerant at the optimum mass ratio (CO2/R41 cycle), a two-stage transcritical cycle with throttling valve using pure CO2 refrigerant (CO2 two-stage cycle) and a single-stage transcritical cycle with expander using pure CO2 refrigerant (CO2 expander cycle) in detail. The results show that the optimum mass ratio of CO2/R41 azeotropy mixture is 0.583/0.417. Comparing with CO2 two-stage cycle and CO2 expander cycle, the attractiveness of CO2/R41 cycle is connected with its simpler structure, obviously lower optimum high pressure, appropriate discharge temperature of compressor and high competitiveness in terms of COP, et al. So, the CO2/R41 azeotropy mixture (0.583/0.417, mass ratio) is eco-friendly and has application potential in industry as a refrigerant. The simple CO2/R41 cycle has the feasibility to replace the complex CO2 two-stage cycle and CO2 expander cycle. The CO2/R41 azeotropy mixture may be a good alternative refrigerant in refrigeration industry.